Knowledge of majority scientific agreement on anthropogenic climate change predicts perceived global risk better than perceived personal risk. Issue 6 (3rd June 2022) - Kohl, Patrice; Wardropper, Chloe
Abstract: Studies examining climate change risk perceptions rarely differentiate between personal and general risk perceptions. Researchers could come to conflicting conclusions about what variables are important in predicting people's perceptions of risk if they do not differentiate between perceptions of personal and general risk. In this study, we used data from a survey of residents in a Midwestern region of the United States to examine the relationship between two measures of knowledge and perceptions of the risk of climate change at personal and the global (i.e. general) levels. Knowledge of the scientific consensus on anthropogenic climate change significantly predicted perceptions of both types of risks, but was more strongly related to greater risk perceptions at the global level. Knowledge of climate change's impact on regional flooding predicted greater climate change risk perception, and we did not find a difference in its association with risk perception at the global versus the personal level. Understanding how different types of knowledge influence peoples' perception of climate change risks can foster a better understanding of related decision-making processes and used to support more strategic public education and communication on climate change. Supplemental data for this article is available online at https://doi.org/10.1080/13669877.2022.2028883 .